2012
DOI: 10.1186/bcr3163
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing mammographic images by using generic texture features

Abstract: IntroductionAlthough mammographic density is an established risk factor for breast cancer, its use is limited in clinical practice because of a lack of automated and standardized measurement methods. The aims of this study were to evaluate a variety of automated texture features in mammograms as risk factors for breast cancer and to compare them with the percentage mammographic density (PMD) by using a case-control study design.MethodsA case-control study including 864 cases and 418 controls was analyzed autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 45 publications
5
57
1
Order By: Relevance
“…2) in either the retroareolar area, 25 the central breast area, 11,23 the largest rectangular box inscribed within the breast, 27 or as a single feature from the entire segmented breast. 28 However, such approaches may be limited, as they cannot fully capture the granularity and heterogeneity of the parenchymal texture. Following the original definition of image texture, [29][30][31][32] mammographic texture should be described as repeated local primitives (i.e., structure elements) estimated over the entire breast.…”
Section: Introductionmentioning
confidence: 99%
“…2) in either the retroareolar area, 25 the central breast area, 11,23 the largest rectangular box inscribed within the breast, 27 or as a single feature from the entire segmented breast. 28 However, such approaches may be limited, as they cannot fully capture the granularity and heterogeneity of the parenchymal texture. Following the original definition of image texture, [29][30][31][32] mammographic texture should be described as repeated local primitives (i.e., structure elements) estimated over the entire breast.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage mammographic density (PD) is an established independent risk factor for breast cancer, and research has also provided evidence that mammographic image texture may contribute differently from PD to breast cancer prediction [2,3,4]. Image-based methods related to breast cancer prediction analyze mammograms of controls and cancer-cases prior to diagnosis, and attempt to predict future incidents of cancer.…”
Section: Introductionmentioning
confidence: 98%
“…To overcome these limitations, recent studies have indicated texture features extracted from mammograms can help improve the prediction accuracy, even when breast density is considered. [27][28][29] Furthermore, we noticed that in most reported studies, computerized features were measured and extracted from the single region of each mammogram, usually the whole breast area, but only a few considered the internal tissue/structural information. 30 The purpose of this study is to develop a new framework for near-term breast cancer risk analysis for multiscale texture measurements on mammograms as well as more accurate and sensitive measurements of breast density.…”
Section: Introductionmentioning
confidence: 99%